Participation of the adrenal gland in the anti-inflammatory effect of polyunsaturated diets - V. L. F. Silveira; E. A. Limãos; D. W. Nunes (Mediators of Inflammation)
The effect of an n-3 (fish) and n-6 (soybean) fatty acid-rich diet on carrageenin paw oedema in rats, and the participation of adrenal gland, corticosterone and α2-macroglobulin (α2-M) in this process were studied. A significant inhibition of carrageenin oedema was observed not only in rats fed a diet rich in fish oil but also in the soybean group. α2-M was not detectable before carrageenin injection, suggesting that this putative antiinflammatory factor does not participate in the observed anti-inflammatory effect. Corticosterone levels were higher in fat-fed than in control rats, before carrageenin stimulus and adrenalectomy abolished the anti-inflammatory response in fat-fed animals, showing the important role of the adrenocortical hormones in this process.